2015
DOI: 10.1016/j.anr.2015.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Health Status and Health Behaviors on Depression Among Married Female Immigrants in South Korea

Abstract: Both health status and health behaviors had significant impacts on depression, suggesting that development of nursing interventions and educational programs should be targeted towards improving maternal health, healthy lifestyle, and subjective health perception to promote married female immigrants' psychological well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…The characteristics of participants influencing depression were age, spouse's age, perceived health, and perceived stress. This result is in line with previous studies reporting that the experience of depression was highest among Koreans in their 60s (Korea Center for Disease Control & Prevention, ); that those who perceived their health as poor complained more of depression symptoms (Kim, Yang, et al, ); and that there is a significant correlation between perceived stress and depression (Kirchner & Patino, ). This study also identified two factors that might play major roles in immigrants’ mental health: life satisfaction and perceived stress.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The characteristics of participants influencing depression were age, spouse's age, perceived health, and perceived stress. This result is in line with previous studies reporting that the experience of depression was highest among Koreans in their 60s (Korea Center for Disease Control & Prevention, ); that those who perceived their health as poor complained more of depression symptoms (Kim, Yang, et al, ); and that there is a significant correlation between perceived stress and depression (Kirchner & Patino, ). This study also identified two factors that might play major roles in immigrants’ mental health: life satisfaction and perceived stress.…”
Section: Discussionsupporting
confidence: 91%
“…Symptoms of depression serve as a predictor of health problems and poor health status, as well as low quality of work including work performance (Lee, Ahn, Miller, Park, & Kim, ). According to a systematic review and meta‐analysis of adult depression in Asian‐American communities, the level of depression in Chinese‐Americans was approximately half that of Korean‐Americans and Filipino‐Americans (Kim, Yang, Chee, Kwon, & An, ).…”
Section: Introductionmentioning
confidence: 99%
“…Five cross-sectional studies reported the prevalence of MIW’s psychiatric problems, notably depression. Using the Center for Epidemiological Studies-Depression Scale (CES-D), these studies reported the prevalence of depression with distinct cut-off scores: with 16 cut-off scores, 39.9% (Kim, Yang, Chee, Kwon, & An, 2015; Kim, Yang, Kwon, & Kim, 2011); with 21 cut-off scores, 9.2%– 26.9% (H. Kim & Kim, 2013; O.…”
Section: Resultsmentioning
confidence: 99%
“…Current findings are consistent with those from previous studies reporting decreased PA as a significant determinant of depression in cross-sectional 16 and longitudinal studies 18 , 19 as well as in a hybrid study involving healthy older women. 31 However, some studies reported a bi-directional relationship between PA and depression. Lampinen et al 32 confirmed in an 8 year-follow-up that elderly persons who reduced activities had higher risks of depressive symptoms compared to those who increased or maintained PA.…”
Section: Discussionmentioning
confidence: 99%